Data Analysis in Automotive Industrial Cells - Martins, Renato Jorge Marçal (2019)
The manufacturing industry always has been one of the leading energy consumers, so companies in this area are always trying to use the best tools provided by the evolution of the technology, to analyse and lower the production costs. Many known studies don’t mind inconveniences such as stopping the production of the factory to perform studies or deep architecture improvements in the transport system. The proposed solution offers two different sets of tools. A device adapter, that targets the gather and storage of data, from industrial robotic cells devices, being the main requirement for a data analysis application, and a data analysis system, that analyses the stored data, without changing the existing production model. The analysis procedure aims the energy usage of a cell and its robot, and the duration of the executed processes. This solution was tested in two different robotic cells, that execute the same process. Multiple executions with different robot velocities were performed in order to gather the required data to provide an analysis and the conclusion was that, for both cells, the energy usage for each executed product was lower when the robot speed was higher, and that one of the cells is more efficient that other cell when executing at high speed but less efficient on lower velocities.